Reasons for delaying the first birth for mothers aged 35 and more - Kozáková, Radka; Vévodová, Šárka; Vévoda, Jiří; Merz, Lukáš (Profese Online, 2015)
Background: Background of research was Psychological studies of late parenthood motives author Bímová (6).Aim: The aim of the research was to determine the reasons for postponing the first birth for mothers after 35 years of age.Methods: The group selection criterion was a primipara age 35 and more. A semi-structured questionnaire of an original design was used to collect the research data. The number of respondents was 92. Data were obtained on obstetric and neonatal departments from January 2013 to January 2014. To analyze the data was used Fisher's exact test.Results: The most frequent reason for birth postponement amongst mothers aged 35 and more was the search for a suitable partner. This option was selected by 42.4% mothers. The second most frequent answer involved issues with conception, this being reported by 32.6% mothers. Additionally, the survey research included a retrospective positive or negative evaluation of the mothers' age when they had their first child after the age of 35. In retrospect, the age for the first birth was seen positively by 45.7% women and negatively by 54.3% women. Women evaluating the age for the first birth negatively significantly more often reported the reason "Problems with conception" (p = 0.014). Women evaluating the age for the first birth positively significantly more often reported "A preference of an independent way of life" as the reason behind their birth postponement (p = 0.039).Conclusions: The reasons for birth postponement of the first child amongst late mothers fell into the areas of social, psychological, and health-medical related issues. The research can lead up to reflection about postponing parenthood. The research can lead up to debate about thinking of risks or benefits of later parenthood.
Keywords: first child; late motherhood; motherhood causes amongst older women; retrospective evaluation